Acute Rejection Clinically Defined Phenotypes Correlate With Long-term Renal Allograft Survival. Issue 10 (October 2015) - Krisl, Jill C.; Alloway, Rita R.; Shield, Adele Rike; Govil, Amit; Mogilishetty, Gautham; Cardi, Michael; Diwan, Tayyab; Abu Jawdeh, Bassam G.; Girnita, Alin; Witte, David; Woodle, E. Steve
Abstract : Background: Classification of acute rejection (AR) based on etiology and timing may provide a means for enhancing therapeutic results and allograft survival. This study evaluated graft and patient survival after the first AR episodes among kidney transplant recipients with an early or late antibody-mediated rejection (AMR), acute cellular rejection (ACR) or mixed AR (MAR). Methods: A prospective institutional review board–approved database was queried to identify biopsy-proven first AR episodes occurring from January 2005 to October 2012. The ACR was defined by Banff criteria; borderline AR was excluded. The AMR was defined as 3 of 4 criteria: renal dysfunction, donor specific antibody, C4d positivity on biopsy, and histological changes. The MAR met criteria for both ACR and AMR. Early AR occurred within six months post-transplant. AR episodes were then assigned to 1 of the 6 categories—early AMR, early ACR, early MAR, late AMR, late ACR, and late MAR. Results: One hundred eighty-two kidney transplant recipients identified with a first AR episode. Mean follow-up was 773 days (±715 days). No difference was observed in patient survival. Death-censored graft survival was 84%. Death-censored graft loss was higher with late versus early AMR ( P = 0.01) and late versus early ACR ( P = 0.03), but not late versus early MAR ( P = 0.3). Conclusions: The AR type demonstrated a hierarchy for graft survival with ACR better than MAR better than AMR, which persisted for both early and late AR. Improvement in long-term results of AR may require development of specific treatment for individual AR types. Abstract : In 182 kidney transplant recipients with a first biopsy-proven rejection, graft prognosis was better in early than in late rejections and also better in cellular than in humoral or mixed rejection outlining the current need for a more specific treatment in each rejection category.